Release of outer membrane vesicles from Bordetella pertussis - Hozbor, Daniela Flavia (1999)
The aim of the study reported here was to investigate the production of Bordetella pertussis outer membrane vesicles (OMVs). Numerous vesicles released from cells grown in Stainer-Scholte liquid medium were observed. The formation of similar vesicle-like structures could also be artificially induced by sonication of concentrated bacterial suspensions. Immunoblot analysis showed that OMVs contain adenylate cyclase-hemolysin (AC-Hly), among other polypeptides, as well as the lipopolysaccharide (LPS). Experiments carried out employing purified AC-Hly and OMVs isolated from B. pertussis AC-Hly− showed that AC-Hly is an integral component of the vesicles. OMVs reported here contain several protective immunogens and might be considered a possible basic material for the development of acellular pertussis vaccines.